Interstitial pneumonia microenvironment promotes metastasis to the mediastinal lymph nodes and lungs - Maeda, Ryo; Inomata, Mayu; Yamada, Ryusei (Frontiers in Oncology, 2025)
IntroductionhtaThe prognosis of patients with lung cancer and interstitial lung disease (ILD) is worse than that of patients without ILDs; however, therapeutic options for ILD-associated lung cancer are severely limited. Although ILD is associated with an increased incidence of lung cancer, it is unclear whether the ILD lung environment affects the biological behavior of lung cancer.MethodsWe tested our hypothesis that the lung environment of ILD is associated with the biological behavior and progression of lung cancer using an in vivo murine model of interstitial pneumonia (IP) and lung cancer.ResultsThe bleomycin-induced IP lung environment promoted metastasis to the mediastinal lymph nodes or contralateral lungs in an orthotopic model of lung cancer. The results of our in vivo experiments were supported by clinical data, which indicated that a significantly greater number of carcinomas with vascular invasion and lymphatic permeation, lymph node metastases, and intrapulmonary metastases were found in patients with clinical stage I non-small cell lung cancer and ILD than in those without ILD. In addition, pharmacological treatment of the IP lung environment with pirfenidone (PFD) inhibited tumor progression in the IP lung cancer model.ConclusionWe found that the IP lung environment promotes lung cancer metastasis. The results of this study may pave the way for further clinical studies on the use of PFD alone or in conjunction with conventional chemotherapy in patients with lung cancer and ILD.